ChemInform Abstract: Synthesis, Structure and Properties of a Co‐Crystallized Complex Based on Polyoxovanadate [VIV12VV6O42] 6‐ and a Mononuclear Vanadium Complex [VON(CH2CH2O)3]. Issue 10 (February 2016) - Wang, Lijuan; Fan, Huitao; Du, Chaojun; Xing, Xiaojing; Zhao, Yingying; Chen, Baokuan; Wang, Liya
Abstract: The co‐crystallized compound (III), based on mixed valence polyoxovanadate [V IV 12 V V 6 O42 ] 6‐ and compound (IV) are solvothermally synthesized and characterized by single crystal XRD, IR, XPS, and magnetic and luminescence measurements.